DIGITAL DECISION-MAKING TECHNOLOGIES: CROWDSOURCING AS A FORM OF POLITICAL PARTICIPATION - O. V. Erokhina (Publishing House of the State University of Management, 2020)
In the era of the fourth industrial revolution, a “smart” society is being formed, whose members are able to acquire and apply new competencies, including in the field of political management. In the field of public policy, this is  related to the creation and implementation of innovations in the public administration system. In this regard,  crowdsourcing is becoming a more popular form of interaction between the government and society, including not only the creation of a “bank of ideas”, but also the use of Internet solutions for new forms of political participation. The key areas of digital interaction between society and the state are the delegation of power to citizens and the introduction of innovations to reduce transaction costs.